Stefna Háskóla Íslands um opinn aðgang: Aðdragandi og viðhorf akademískra starfsmanna háskólans - Áslaug Agnarsdóttir 1949- (2015)
Only two universities in Iceland have adopted an open access policy. Bifröst University was the first Icelandic university to publish an open access policy in 2012. In November 2011 the University of Iceland formed a working group with representatives from each of the five schools as well as a representative from the National and University Library of Iceland. The working group was to draft an open access policy for discussion within and eventual acceptance by the academic community and submit the draft to the University administration before April 1st 2012. This article discusses the work involved in drafting the mandate and the ensuing debate among the academic staff. The preliminary draft was submitted by the end of March of that year as well as recommendations and suggestions from the working group on a few issues that need to be considered such as the unavoidable cost, complex copyright issues and negotiations with publishers. The main concerns of the academic community included impairment of freedom of research, poor peer review, the impact on Icelandic publishing and books. Nearly two years after the working group submitted the draft the final policy was approved by the University of Iceland in February 2014. It had however not been implemented in November of that same year.